ANALYSIS OF THE REQUIREMENTS OF THE SPINNING ENTERPRISES OF UZBEKISTAN AND THE WORKING CONDITIONS IN IT - Gafurova N. T; Xojayeva M.E (Scholar Express Journals, 2024)
This article investigates the current state and future prospects of spinning enterprises in Uzbekistan, with a particular focus on labor conditions. The study explores various aspects of the spinning industry, evaluates existing labor conditions, and provides recommendations for improvements. Using a combination of literature review, field studies, and statistical analysis, this research aims to provide a comprehensive overview of the challenges and opportunities facing Uzbekistan's spinning sector
Keywords: Uzbekistan; spinning enterprises; labor conditions